Hubungan Stress Kerja Dengan Quality of Nursing Work Life Pada Perawat di Ruang Rawat Inap Rumah Sakit Dustira - Nugraheni, Fatimah Rizka; Oyoh, Oyoh; Setiawati, Setiawati; Rohayani, Lilis (Yayasan Healing and Healthcare Education, 2025)
Quality of nursing work life is a major focus in healthcare organisations and impacts nurses and nursing services. A decline in nurses' quality of work life can leave them feeling frustrated, inadequate and guilty. The inability to cope with these issues can be detrimental to health and cause stress. Occupational stress arises when work does not match abilities and needs, which can cause negative physical and emotional reactions. Based on this phenomenon, this study aims to determine the relationship between job stress and quality of nursing work life in nurses in the inpatient room.The research design used was an analytical survey with a cross sectional approach. Sampling was done by purposive sampling as many as 38 people. Data were collected by questionnaire. Univariate (frequency distribution) and bivariate data analysis (Chi-Square) was conducted. Based on univariate results, the results of work stress were low (52.6%) and high (47.4%), quality of nursing work life was low (52.6%) and high (47.4%). The results of statistical tests with Chi-Square obtained a P value of 0.049 (p <0.05), it can be concluded that there is a relationship between job stress and quality of nursing work life in Nurses in the Inpatient Room. To enhance the quality of nurses' work life, hospitals should implement stress management programs that offer relaxation techniques and psychological support.